Predictive factors for intraoperative excessive bleeding in Grave’s disease - Srinivas, A. (International Surgery Journal, 2020)
Background: Grave’s disease frequently results in and is the most common cause of hyperthyroidism. It also often results in an enlarged thyroid. It also known as toxic diffuse goiter, is an autoimmune disease that affects the thyroid. This study evaluates all the factors that cause intra-operative blood loss and how it affects the grave’s disease. Methods: This study was conducted on 100 patients with Grave’s disease, who underwent thyroidectomy during the period from May 2010 to April 2016. Results: The majority of patients were females which constitute about 76.3% with a median age of 33 years. The median period between the onset of the disease and operation was 15 months. Weight of thyroid in grams was 40. Post-operative hospital stay was 3 days. Univariate analysis revealed that the strongest correlation of amount of intraoperative blood loss (AIOBL) was noted with the weight of thyroid (p<0.001). Additionally, AIOBL was correlated positively with the period be- tween disease onset and surgery (p<0.001) and negatively with preoperative free T4 (p<0.01). Occurrences of postoperative complications, such as recurrent laryngeal nerve palsy or hypoparathyroidism, and postoperative hospital stay were not correlated with AIOBL. Conclusions: For Grave’s disease, for excessive bleeding during surgery, a large goiter presented as a predictive factor, and transfusion of blood should be considered in cases in which goiter weighs more than 200 g.